Pharmacokinetics studies of single orally administered 1, 3, 4-thiadiazoles: method development and validation. (November 2017) - Raj, Vinit; Rai, Amit; Singh, Ashok K; Keshari, Amit K; Saha, Sudipta
Aim: The main objective was to determine and quantify 1, 3, 4, thiadiazoles scaffold (VR24 and VR27) in rat plasma using HPLC−UV pharmacokinetic approach.Materials & methods: A rapid and sensitive reverse phase-HPLC was adopted for the determination of V24 and VR27 in rat plasma. Both were separated on Shimadzu reverse phase-C18 column (5.0 µ and 4.6 × 250 mm) by a gradient elution of acetonitrile and water with 1 ml/min flow rate. The detector was set at 270 and 275 nm for VR24 and VR27, respectively, with an elution time of 3.37 and 3.86 min.Results: The calibration range was 0.1–10 µg/ml with r 2 of 0.974 and 0.987, respectively. The inter- and intra-day variations of the assay were lower than 15.21%; the average recoveries of VR24 and VR27 were 94.2 and 91.5% with RSD of 4.01 and 2.03%, respectively, signified the robust method of detection in our experiment. The Cmax and Tmax were ∼0.528, 5.55 µg/ml and 4.0, 2.0 h, respectively, for VR24 and VR27.Conclusion: The outcome from this study indicated that both compounds had a lower rate of absorption, higher volume of distribution and lower clearance rate, indicating good therapeutic potential for in vivo therapy. Graphical abstract: